Interação intérprete – compositor: registro e reflexão do processo criativo na concepção da obra Quid credas continuum Quid agas - Silva, Rudson Ricelli Lima da (2016)
The present work deals with the report on the interaction interpreter-composer, lined with individual biases - mediated by the interpreter-researcher Rudson Ricelli Lima da Silva - and collectives - of the composer Samuel Cavalcanti Correia with the group Trompetearte of EMUFRN. For this, during the project phase, we idealized the making of a work especially to materialize the interests of the present research, where only the instrumentation to be used was determined. From the pre-project, the trumpet quintet formation was suggested, using the main instruments of the family (in Si¨, Dó, Mi¨, piccolo, and fluguelhorn). The methodology developed for this research was accomplished through the fulfillment of an agenda of meetings previously elaborated, constituted of a series of stages and organized in two phases, where we approach the interaction from the first creative impulses of the composer and his creative resourcefulness. We also present the preparation of excerpts from the work in the course of trial-experiments, as well as the construction of an interpretation and results / consequences from this interaction.